Probiótico como alternativa a antibiótico para frangos de corte desafiados com Salmonella Heidelberg - Cirilo , Edinan Hagdon (2022)
The objective of this work was to evaluate the use of probiotics in the bedding and diets of broilers challenged with Salmonella Heidelberg (SH) on performance, carcass and cuts yield, relative liver and fat weight, blood biochemical parameters, intestinal morphometry, cecal contamination by SH and litter quality. For that, 640 one-day-old male broiler chicks were used, distributed in a completely randomized design with five treatments, eight replications and 16 birds per experimental unit (UE). The treatments consisted of: a positive control (CP – basal chow with the use of enramycin and salinomycin), a negative control (CN – basal chow without enramycin and salinomycin), a third treatment with CN chow plus inclusion of 1 kg ton-1 of probiotic in the ration, a fourth treatment with CN ration plus application of 20 g m-2 of probiotic in the litter and a fifth treatment with CN ration with the inclusion of 1 kg ton-1 of probiotic in the ration and the application of 20 g m- 2 probiotic in bed. The application of the probiotic in the bed was carried out 5 days before the accommodation. At 3 days of age, 4 birds per UE received a SH culture inoculum solution (106 UFC bird-1) by gavage. Performance at 21 and 42 days (weight gain, feed intake and feed conversion), carcass and cuts yield, relative liver and fat weight at 42 days, blood biochemical profile at 40 days, jejunum morphometry at 28 days were evaluated. days, Salmonella spp. count in the cecum at 14 and 28 days and litter quality parameters at 28 and 40 days (dry matter, pH and ammonia). Data were submitted to analysis of variance and Tukey's test at 5% probability was used to compare significant variables. The results of counting Salmonella spp. showed no normal distribution, so the Kruskal-Wallis test was used. In the initial phase (1 to 21 days) it was observed that the birds that received antibiotic ration and those that received probiotic in the ration presented better results (P<0.05) of CA, as well as the treatment that received probiotics in the ration and in the bed. At the end of the experimental period, there was a lower CMR (P<0.05) of the treatments with probiotic in the ration and probiotics in the ration and in the bedding and a better result (P<0.05) of CA for the probiotic in the ration and into bed. The use of probiotic did not change carcass and cuts yield, as well as blood biochemical parameters and intestinal morphometry. The use of the probiotic in the diets and in the litter provided a better performance in birds from 1 to 42 days of age, promoted an improvement in the quality of litter at 28 days of age, with lower ammonia concentration and lower humidity. It can be concluded that the probiotic improves performance, does not change intestinal morphometry, serum metabolites and hepatic and renal metabolism of birds and improves litter quality at 28 days.